Critical Review on Sushruta’s Management of Bhagna: Life Sciences-Medicine - Jaivarshaa GV, Dr. Pavithra; Dasar, Dr. Devyani; Biswas, Dr. Shubham; Singh, Dr. Naveen; Mavale, Dr. Abhishek (International Journal of Life Science and Pharma Research, 2022)
Right from ancient years to contemporary times, trauma care has been an important goal of emergency management. Orthopedic injuries have a high incidence and remain a significant challenge for trauma care. Sushruta Samhita has an extensive description of the management of orthopedic injuries like fractures and dislocations. According to Ayurvedic scriptures, a fracture is the loss of the bone’s continuity due to pressure. The fundamental principles of fracture therapy, such as Reduction, Immobilization, and Rehabilitation, are used to treat long bone fractures. Many indigenous substances that can aid in fracture healing are documented in ancient treatises. This study aimed to explore the types and management protocol of fracture Acharya Sushruta. The method was followed to analyze Sushruta Samhita, its commentaries, and Internet surfing from various research articles. In Sushruta Samhita, the maximum information about the disease fracture, its classification, and symptoms are elaborated in the fifteenth chapter of nidan sthan and its management was described in the third chapter of chikitsa sthan along with extensive details of surgical and non-surgical management, dietetic indications and local applications. Ancient surgeons prioritized fractures of the pelvic area, spines, long bone shafts, and thighs, among various fractures. The rules established by Acharya Sushruta are so authentic that even today’s orthopedic surgeons follow them. Traction and retention were used after Unnamana (elevation of the depressed fragment) and Vinamana (depression of elevated fragment) while managing shattered bones. Sudha varga dravyas were used in compound fractures, multiple fractures, and irregular fractures when the broken section is completely separated or missed in certain circumstances. As a graft material, a paste made from the decoction of Rubia cordifolia, Sudhavarga dravya, and latex of Ficus Benghalensis was applied. The research provided a thorough literature review on fracture and fundamental principles, which are valid even in today’s orthopedics.